1998
DOI: 10.1074/jbc.273.35.22466
|View full text |Cite
|
Sign up to set email alerts
|

HYAL2, a Human Gene Expressed in Many Cells, Encodes a Lysosomal Hyaluronidase with a Novel Type of Specificity

Abstract: Using Expressed Sequence Tags (ESTs) deposited in the data banks, a cDNA has been assembled that encodes a protein related to the hyaluronidases from bee venom and mammalian sperm. Expression of this cDNA yielded a polypeptide termed HYAL2, which is located in lysosomes. The HYAL2 protein was shown to have hyaluronidase activity below pH 4. However, it only hydrolyzed hyaluronan of high molecular mass from umbilical cord, rooster comb, and a Streptococcus strain. The reaction product was a polysaccharide of ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
224
3
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(244 citation statements)
references
References 26 publications
15
224
3
2
Order By: Relevance
“…HYAL2 (hyaluronidase 2, also known as LUCA2) is expressed at high levels in most tissues (including heart, placenta, lung, liver, skeletal muscle and kidney) but absent or poorly expressed in brain (Lepperdinger et al, 1998;Csoka et al, 1999;Lerman and Minna, 2000). Loss of expression in adult brain is reported to be due to promoter methylation (Lepperdinger et al, 2001).…”
Section: Hyal2/luca2mentioning
confidence: 99%
See 2 more Smart Citations
“…HYAL2 (hyaluronidase 2, also known as LUCA2) is expressed at high levels in most tissues (including heart, placenta, lung, liver, skeletal muscle and kidney) but absent or poorly expressed in brain (Lepperdinger et al, 1998;Csoka et al, 1999;Lerman and Minna, 2000). Loss of expression in adult brain is reported to be due to promoter methylation (Lepperdinger et al, 2001).…”
Section: Hyal2/luca2mentioning
confidence: 99%
“…The HYAL2 gene ( Figure 2a) encodes a 473 amino-acid protein ( Figure 2b) with a signal peptide (amino acids 1-20), and a calcium binding epidermal growth factor (EGF)-like domain (amino acids 365-469 by SMART prediction). Green fluorescent protein-tagged HYAL2 was shown to have a lysosomal localization (Lepperdinger et al, 1998), but subsequent work has suggested that HYAL2 is actually a cell surface glycosylphosphatidylinositol anchored protein (Rai et al, 2001). Although there is some evidence that it may also be produced in a soluble form.…”
Section: Hyal2/luca2mentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, mammalian hyaluronidases were uncharacterized enzymatic activities present in many tissues, distinguished only on the basis of their pH optima. In the human, it is now established that at least six hyaluronidase-like sequences occur in the human genome, three each at two chromosomal locations: HYAL1, HYAL2, and HYAL3 at chromosome 3p21 (Lepperdinger et al, 1998; Cso ka et al, 1999); and HYAL4, SPAM1, and HYALP1 at chromosome 7q31 (Cso ka et al, 1999). The gene for Hyal-2, HYAL2, a recently identi®ed lysosomal hyaluronidase (Lepperdinger et al, 1998) resides immediately centromeric to HYAL1 on 3p21.3.…”
Section: Introductionmentioning
confidence: 99%
“…In the human, it is now established that at least six hyaluronidase-like sequences occur in the human genome, three each at two chromosomal locations: HYAL1, HYAL2, and HYAL3 at chromosome 3p21 (Lepperdinger et al, 1998; Cso ka et al, 1999); and HYAL4, SPAM1, and HYALP1 at chromosome 7q31 (Cso ka et al, 1999). The gene for Hyal-2, HYAL2, a recently identi®ed lysosomal hyaluronidase (Lepperdinger et al, 1998) resides immediately centromeric to HYAL1 on 3p21.3. Hyal-2 possesses an apparent speci®city for high molecular weight HA (420 kDa) and is expressed in all tissues except the brain.…”
Section: Introductionmentioning
confidence: 99%